Analisis Indikator Kinerja Pelaksanaan Anggaran (IKPA) di Kementerian Desa Pembangunan Daerah Tertinggal dan Transmigrasi Tahun Anggaran 2020–2022 - Irlian, Daffa; Perdana, Petrolis Nusa; Zairin, Gentiga Muhammad (Jurnal Akuntansi, Perpajakan dan Auditing, 2025)
This research was conducted to analyze the Budget Implementation Performance Indicators (IKPA) in the Ministry of Village Development of Underdeveloped Areas and Resettlement for the Budget Years 2020-2022. This study used a qualitative approach with a descriptive research design. The study obtained primary data from semi-structured interviews between the researcher and employees of the Ministry of Village Development of Underdeveloped Areas and Resettlement, as well as secondary data from the IKPA results for the budget years 2020-2022. Based on the results of the research, it was concluded that there were fluctuations in the weight of the IKPA value received by the Ministry of Village Development of Disadvantaged Regions and Transmigration. In the fiscal year 2020, the value was 89.83, obtained from 13 indicators, each with the following scores: Revisi DIPA: 87.50, Deviasi Halaman III DIPA: 71.29, Pagu Minus: 100, Data Kontrak: 86, Pengelolaan UP dan TUP: 100, LPJ Bendahara: 100, Dispensasi SPM: 0, Penyerapan Anggaran: 100, Penyelesaian Tagihan: 100, Konfirmasi Capaian Output: 100, Retur SP2D: 99.84, Renkas: 100, Kesalahan SPM: 80. In the fiscal year 2021, the score was 88.50, obtained from 13 indicators, each with the following scores: Revisi DIPA: 100, Deviasi Halaman III DIPA: 57,23, Pagu Minus: 100, Data Kontrak: 82, Pengelolaan UP dan TUP: 92, LPJ Bendahara: 100, Dispensasi SPM: 100, Penyerapan Anggaran: 61.42, Penyelesaian Tagihan: 100, Capaian Output: 100, Retur SP2D: 97.32, Renkas: 100, Kesalahan SPM: 80. In the fiscal year 2022, the score was 91.87, obtained from 8 indicators, each with the following scores: Revisi DIPA: 100, Deviasi Halaman III DIPA: 69,03, Penyerapan Anggaran: 85,16, Belanja Kontraktual: 88,65, Penyelesaian Tagihan: 94,38, Pengelolaan UP dan TUP: 96,38, Dispensasi SPM: 100, Capaian Output: 99,99.